2020
DOI: 10.3390/polym12010129
|View full text |Cite
|
Sign up to set email alerts
|

Acidity Suppression of Hole Transport Layer via Solution Reaction of Neutral PEDOT:PSS for Stable Perovskite Photovoltaics

Abstract: Poly(3,: poly(4-styrenesulfonate) (PEDOT:PSS) is typically used for hole transport layers (HTLs), as it exhibits attractive mechanical, electrical properties, and easy processability. However, the intrinsically acidic property can degrade the crystallinity of perovskites, limiting the stability and efficiency of perovskite solar cells (PSCs). In this study, inverted CH 3 NH 3 PbI 3 photovoltaic cells were fabricated with acidity suppressed HTL. We adjusted PEDOT:PSS via a solution reaction of acidic and neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
0
24
0
1
Order By: Relevance
“…It is well known that OSCs with PEDOT:PSS are very vulnerable to degradation due to the acidic nature of the HEL, which deteriorates the adjacent active layer polymer and fullerene derivatives. [19][20][21][22][23][24] In line with these studies, devices with PEDOT:PSS showed unstable J SC and FF, which decreased by 70% and 29%, resulting in a PCE drop of 80%, aer 2 days. Aer 4 days of degradation, the PCE showed a total decrease of 87%.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…It is well known that OSCs with PEDOT:PSS are very vulnerable to degradation due to the acidic nature of the HEL, which deteriorates the adjacent active layer polymer and fullerene derivatives. [19][20][21][22][23][24] In line with these studies, devices with PEDOT:PSS showed unstable J SC and FF, which decreased by 70% and 29%, resulting in a PCE drop of 80%, aer 2 days. Aer 4 days of degradation, the PCE showed a total decrease of 87%.…”
Section: Resultsmentioning
confidence: 63%
“…However, because of the acidic nature of PEDOT:PSS, it is also well known that PEDOT:PSS deteriorates the adjacent layers, resulting in poor device stability. [19][20][21][22][23][24] Furthermore, the unignorable absorption hurdles prevent realization of the potential efficiency of OSCs. 25,26 Transition metal oxides (TMOs) are also a good option for HELs.…”
Section: Introductionmentioning
confidence: 99%
“…The fast degradation of the PEDOT:PSS-only device could be due to its acidic [58,59] and hygroscopic [60] nature, decaying the transparent conducting oxide (FTO) and/or the photoactive layer, which is sensitive to moisture. It could also be a result of morphological inhomogeneity with rougher interfaces.…”
Section: Performance Of Fabricated Perovskite Solar Cellsmentioning
confidence: 99%
“…Similarly, PSCs with PEDOT:PSS as HTM often prepared in high acidity conditions results in device distortion. 44 ITO substrate was reported to be degrading when in direct contact with hygroscopic PSS that shows the capability to absorb moisture from the atmosphere, which limits the hole extraction through ITO/PEDOT:PSS interface. 45 This limit has resulted in the use of inorganic HTM; for instance, copper (I) thiocyanate (CuSCN) due to its stability against moisture and heat.…”
Section: Working Principle and Device Componentsmentioning
confidence: 99%
“…The dopant reported tends to introduce moisture to the perovskite material due to its corrosive and hygroscopic nature. Similarly, PSCs with PEDOT:PSS as HTM often prepared in high acidity conditions results in device distortion 44 . ITO substrate was reported to be degrading when in direct contact with hygroscopic PSS that shows the capability to absorb moisture from the atmosphere, which limits the hole extraction through ITO/PEDOT:PSS interface 45 .…”
Section: Introductionmentioning
confidence: 99%